Pengaruh Kemudahan dan Risiko terhadap Keputusan Pembelian Menggunakan SPaylater di Kota Bekasi - Lubis, Nisa Aliya Yahya; Permadi, Hendra; Masrifah, Ifah (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of ease of use and risk on purchasing decisions using Shopee Paylater in Bekasi City. Shopee Paylater is a payment service that allows users to make transactions with an installment system without a credit card. The method used is quantitative, with a survey conducted on 100 Shopee Paylater users, employing purposive sampling. Data were analyzed using SmartPLS version 4 to examine the relationship between the variables of ease of use and risk on purchasing decisions. The results show that ease of use has a positive and significant effect on purchasing decisions, where factors such as easy access, fast transaction processes, and payment flexibility are the main attractions for consumers. Conversely, risk has a significant negative effect on purchasing decisions, with consumers’ concerns about high interest rates, late payment fines, and potential personal data leakage being the primary factors that reduce their interest in using this service.